Spiritual needs throughout childbirth: a cross-sectional study among working women at the largest university in Brunei - Adnan, Ahmad Shamil Haji Mohd; Rahman, Hanif Abdul; Sharbini, Sharimawati; Abdul-Mumin, Khadizah H. (Jurnal Ners, 2024)
Introduction:  This study evaluates spiritual needs throughout childbirth of women who are working in higher education setting. Methods: Healthcare professionals have fundamental roles in ensuring the spiritual needs of women throughout childbirth are met. This concurs with the World Health Organization’s definition of health that holistically comprises of physical/biological, psychological/mental, social and spiritual aspects. This study evaluates spiritual needs throughout childbirth of women who are working in higher education setting. Results: A total 80 female staff participated in the study. Three out of the five domains of the spiritual needs scale were found to be the most frequently addressed as interpreted from the mean score. These are: “Finding meaning and purpose” 4.2 (0.6) followed by “Religious needs” 4.1 (0.7) and “Seeking peace” 4.0 (0.6).  Those aged 40 and above scored 4.3 (0.8), which is significantly higher (P = 0.048) for “Finding meaning and purpose” compared to other age groups. Those who had four or more children had significantly higher spiritual needs for “Finding meaning and purpose” 4.2 (0.6) and “Seeking peace” 4.4 (0.7) compared to those having one to three children. Conclusions: The findings of this study suggest that spiritual needs are essential during childbirth. “Finding meaning and purpose” and “Seeking peace” were identified to be the most common spiritual needs during childbirth. As women age and have more children, their spiritual needs increase. This study contributes positively toward the improvement of care, particularly spiritual aspects where evidence is scarce. Keywords: Assessment, Brunei, Childbirth, Women, Spiritual